2019
DOI: 10.1108/jmtm-12-2018-0459
|View full text |Cite
|
Sign up to set email alerts
|

Achieving automotive suppliers’ mass customization through modularity

Abstract: Purpose Previous literature tends to combine postponement and modularity or view them as parallel factors to achieve mass customization (MC) while ignoring the sequence of a firm to design and implement operations and supply chain strategy. Based on a customer-oriented strategy and theories of organizational information processing theory, three-dimensional (3D) concurrent engineering and resource dependency, the purpose of this paper is to propose a sequential model reflecting the sequence of practices as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…This is based on the following principles. In the Harris algorithm, g x and g y reflect the gray level change direction of each pixel of the image, and if the brightness of pixel ( x , y ) changes sufficiently in all directions, it is extracted as a corner [ 13 ]. The wavelet Ψ u , s ( t ) is a function with a mean of 0, and the wavelet transform of the signal g is …”
Section: Methodsmentioning
confidence: 99%
“…This is based on the following principles. In the Harris algorithm, g x and g y reflect the gray level change direction of each pixel of the image, and if the brightness of pixel ( x , y ) changes sufficiently in all directions, it is extracted as a corner [ 13 ]. The wavelet Ψ u , s ( t ) is a function with a mean of 0, and the wavelet transform of the signal g is …”
Section: Methodsmentioning
confidence: 99%
“…Various authors have reported the effects of different operational strategies and practices on MCC such as modularity (Wang et al , 2014), supply chain integration (Hsuan Mikkola and Skjøtt-Larsen, 2004; Lai et al , 2012), management of demand and supply uncertainties (Liu et al , 2010), supplier lead-time reduction (Tu et al , 2001), internal/external learning and effective implementation of processes (Huang et al , 2008), functional integration (Liu et al , 2012), logistics management (van Hoek, 2000), customization knowledge utilization and business process improvements (Wang et al , 2014), strategic orientation (Wang et al , 2015), absorptive capacity (Zhang et al , 2015), standardization and innovation (Wang et al , 2016), human resource management (Sandrin et al , 2018), individual competencies (Trentin et al , 2019), operational alignment and implementation of postponement (Wu et al , 2019), customer relationship management and organizational culture (Ullah and Narain, 2020a), flexible manufacturing competence and workforce management practices (Ullah and Narain, 2020b) and concluded that to ensure the success of a MC system, organizations should focus on the implementation of practices which could lead to a high level of flexibility and responsiveness.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Within the past decade, heightened competition and ever-growing demand of customers has posed countless challenges to organizations of all sizes (Matthyssens, 2019), and mass customization (MC) has recently been mentioned as an approach to cope with these challenges (Wu et al , 2019). MC can be defined as a business strategy that aims to fulfill the distinct needs of customers at affordable prices and time (Ullah and Narain, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Manufacturing flexibility is believed to be critical in MC (Nawanir et al, 2020). Based on modular theory, manufacturing flexibility is characterized by the ability to adapt to small-batch and multivariety customized production through modules integration (Wu et al, 2019).…”
Section: Mediating Effect Of Manufacturing Flexibilitymentioning
confidence: 99%